La legge organica per le Università israelitiche piemontesi del 1857. Il dibattito e le scelte del Parlamento subalpino (Stato, Chiese e pluralismo confessionale, 2023)
SOMMARIO - 1. L’emancipazione dei culti tollerati e la condizione giuridica degli ebrei piemontesi al momento dello Statuto Albertino - 2. Primi tentativi di riordino delle Università israelitiche (1849-1856) - 3. Il progetto di Riforma degli ordinamenti amministrativi ed economici del culto israelitico (1857) - 4. La Sinistra radicale in dissenso. Riccardo Sineo e i ‘diritti di libertà’ degli israeliti - 5. Alla ricerca di un juste milieu.The Organic Law for the Piedmontese Israelite Communities of 1857. The debate and the choices of the Subalpine ParliamentABSTRACT: This essay aims to reconstruct the story of the enactment of the organic law for Piedmont's Israelite Communities (n. 2325), which in 1857 the Subalpine Parliament approved at the end of a close political debate. In the aftermath of the emancipation - granted in 1848 by Charles Albert to the religious minorities, Waldensian and Israelite, present in the Kingdom of Sardinia - the leaders of the Israelite Communities asked the Savoy government to regulate by law the legal-administrative structure of the community institutions. It was only through a legislative measure, in fact, that the Israelite Communities would be able to retain the privilegia fisci, such as the right to levy taxes on their members and to collect communal taxes through tax-collecting rolls, which until then they had exercised under special pre-statutory provisions. The organic law passed by Parliament recognized the Israelite Communities as necessary corporations, each of which included all Jews residing in the municipality of erection, thus incardinating them into the order of the State, which exercised control and protection over them.